2020
DOI: 10.15252/embj.2020105802
|View full text |Cite
|
Sign up to set email alerts
|

Roles of plant retinoblastoma protein: cell cycle and beyond

Abstract: The human retinoblastoma (RB1) protein is a tumor suppressor that negatively regulates cell cycle progression through its interaction with members of the E2F/DP family of transcription factors. However, RB-related (RBR) proteins are an early acquisition during eukaryote evolution present in plant lineages, including unicellular algae, ancient plants (ferns, lycophytes, liverworts, mosses), gymnosperms, and angiosperms. The main RBR protein domains and interactions with E2Fs are conserved in all eukaryotes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 228 publications
(275 reference statements)
1
69
0
Order By: Relevance
“…The LECA cell cycle network also likely included at least one CDK and multiple cyclins that regulated events in different phases of the cell cycle ( Figure 1 B). Studies from a variety of eukaryotes have demonstrated how RB and E2F homologs link the activity of CDKs with the periodic expression of genes important for cell cycle progression and cell division [ 13 , 17 , 27 ]. Phosphorylation of RB by D-type cyclin-CDKs initially allows the induction of genes important for the G1/S phase transition, including G1/S phase cyclins, like human CCNE (cyclin E) and CCNA (cyclin A).…”
Section: Evolutionary History Of E2f and Rb Homologs In Eukaryotesmentioning
confidence: 99%
See 3 more Smart Citations
“…The LECA cell cycle network also likely included at least one CDK and multiple cyclins that regulated events in different phases of the cell cycle ( Figure 1 B). Studies from a variety of eukaryotes have demonstrated how RB and E2F homologs link the activity of CDKs with the periodic expression of genes important for cell cycle progression and cell division [ 13 , 17 , 27 ]. Phosphorylation of RB by D-type cyclin-CDKs initially allows the induction of genes important for the G1/S phase transition, including G1/S phase cyclins, like human CCNE (cyclin E) and CCNA (cyclin A).…”
Section: Evolutionary History Of E2f and Rb Homologs In Eukaryotesmentioning
confidence: 99%
“…RB homologs in animals and plants actively repress transcription by interacting with and recruiting chromatin modifying enzymes to the promoters of E2F target genes [ 13 , 17 , 27 , 35 , 36 ]. Several of these chromatin modifying enzymes contain a LxCxE amino acid motif that binds to a conserved cleft in the RB pocket domain and allows RB to bind both the chromatin modifiers and E2F factors simultaneously [ 37 ].…”
Section: Evolutionary History Of E2f and Rb Homologs In Eukaryotesmentioning
confidence: 99%
See 2 more Smart Citations
“…The occurrence and development of RB are closely related to the pathogenic variant of the tumor suppressor RB1 gene [7]. Since the 1980s, the RB1 gene on the long arm of chromosome 13 (13q14) has been recognized as the RB tumor suppressor gene for the first time, and its pathogenic variant is involved in the occurrence of RB [5,6,[8][9][10]. Compelling studies [1,5,6,[11][12][13][14][15] indicated that the RB1 gene is an allele encoding retinoblastoma protein (pRB), and the lack of monitoring or inactivation of RB1 will lead to a decline in cell proliferation regulation function thus resulting in abnormal cell proliferation.…”
Section: Introductionmentioning
confidence: 99%